Illuminasi Suhrawardi Al-Maqtūl Sebagai Basis Ontologi Filsafat Etika - Anwar Ma'rufi (Indonesia, 2021)
It is difficult to find a study of ethical philosophy issues in the history of Islamic civilization. The reason is because it was not written separately by Muslim thinkers. It is discussed in tandem with or mixed with other reviews, such as mixed with reviews of metaphysics, psychology, and so on. This paper attempts to reconstruct the philosophy of ethics in Suhrawardi al-Maqtul's thought through the metaphysical theory that he offers. This is qualitative research that is categorized in the type of library research. The field of research is Suhrawardi's work in the form of text, therefore the method used is hermeneutics. More precisely, the hermeneutics used are the hermeneutics of intentionalism and the hermeneutics of Paul Ricoeur. This research shows that Suhrawardi has provided a well-established ontological view for developing ethical concepts. Suhrawardi symbolically identifies good with light (al-nūr) and bad with darkness (ẓulm). Become a perfect human being when the soul is able to let go of the elements of darkness and merge with the light of goodness. The ethical concept offered by Suhrawardi tends to be mystical-rationalist like his big ideas that accommodate Sufism that is harmonized with philosophy.